RAISING AWARENESS OF VILLAGE ARCHIVES ORDERLY THROUGH RECORD MANAGEMENT ASSISTANCE PROGRAM BASED ON SIMULATION VIDEO - Ismiyati, Ismiyati; Pramusinto, Hengky; Marimin, Marimin; Handayani, Bestari Dwi; Sholikah, Mar'atus (Indonesian Journal of Devotion and Empowerment, 2020)
Tujuan dari kegiatan pengabdian kepada masyarakat ini adalah untuk meningkatkan pengetahuan aparatur desa dan meningkatkan kesadaran akan pentingnya tertib arsip di Desa Kenteng. Upaya meningkatkan keterampilan dan kesadaran aparat desa dalam mengelola arsip sesuai kaidah yang berlaku dilakukan melalui pendampingan teknis penataan arsip sesuai kaidah kearsipan di lingkungan pemerintahan. Hasil dari kegiatan masyarakat ini menunjukkan partisipasi peserta sangat tinggi dalam kegiatan webinar record management. Kegiatan webinar berkaitan dengan teknik penataan arsip. Kegiatan webinar dimaksudkan sebagai pengganti kegiatan sosialisasi secara langsung, karena masa pandemi COVID-19 mengharuskan segala bentuk kegiatan tatap muka dikurangi. Untuk itu, kegiatan pengabdian dilakukan dengan acara webinar. Setelah diberikan webinar, dilanjutkan dengan pendampingan teknis kearsipan dengan cara simulation video di lapangan tentang penataan kembali arsip sesuai klasifikasi yang ada, dengan tujuan agar aparatur desa tertib akan arsip. Selain itu, arsip yang dibutuhkan dapat mudah ditemukan kembali. Evaluasi kegiatan webinar dan pendampingan penataan arsip ini menunjukkan bahwa seluruh aparatur desa menunjukkan peningkatan dalam kemampuan dan kesadaran terhadap tertib arsip desa. The purpose of this community service activity is to increase the knowledge of village apparatus and raise awareness of the importance of orderly archives in Kenteng Village. Efforts to improve the skills and awareness of village officials in managing archives in accordance with applicable rules are carried out through technical assistance in the arrangement of archives in accordance with archival rules in the government environment. The results of this community activity showed very high participation of participants in record management webinar activities. Webinar activities related to archival structuring techniques. Webinar activities are intended as a substitute for direct socialization activities, as the COVID-19 pandemic requires all forms of face-to-face activities to be reduced. Therefore, devotional activities are carried out with webinar events. After being given a webinar, followed by archival technical assistance by means of simulation video in the field about the rearranging of archives according to existing classifications, with the aim of orderly village apparatus will archive. In addition, the required archives can be easily rediscovered. Evaluation of webinar activities and assistance in the arrangement of this archive shows that all village apparatus shows improvement in the ability and awareness of the orderly village archives.